Hepatitis B in Poland in 2014 - Stępień, Małgorzata; Piwowarow, Katarzyna; Czarkowski, Mirosław P (Przegląd epidemiologiczny, 2016)
The aim of the study was to assess the epidemiological situation of hepatitis B in Poland in 2014 in comparison with the previous years. The evaluation of the epidemiological situation was carried out on a basis of analysis of data from case-based reports on acute hepatitis B registered by sanitary and epidemiological stations, aggregate data derived from annual bulletins “Infectious diseases and poisonings in Poland”, data from annual bulletin “Vaccinations in Poland” and data on locally registered HBsAg carriers. In 2014, a total of 2,763 cases of hepatitis B were registered, including 36 cases of HBV and HCV co-infections. Acute cases accounted for 2.5% of all HBV cases, the incidence was 0.18 per 100,000 and was slightly lower than in 2013. In the age group of children up to 14 years which were subject to universal vaccination as neonates, acute infections were not identified, in the age group 15-19 years vaccinated at the age of 14 one acute hepatitis B case was reported . Probably, 75% of acute hepatitis B cases occurred in connection with medical procedures carried out in health care facilities. The incidence of chronic and unknown stage of hepatitis B was 7.0 per 100,000 population and was higher by 85% compared to the previous year. The change in the incidence of chronic and UNK hepatitis B observed is related to the modification of case definition for hep B used in the surveillance in 2014 and changes in the regulations on reporting entities. Chronic and UNK cases were noted 1.4-fold more frequently in men than in women and were 1.5-fold more common among urban than rural dwellers. Great differences in incidence maintain between voivodeships, the highest incidence of chronic hepatitis B was recorded in śląskie voivodeship - 14.5 per 100,000 population. In 2014, 7 people died due to acute hepatitis B, and 44 due to chronic hepatitis B. Legislation changes in the epidemiological surveillance implemented in 2014 allowed for a more complete assessment of the epidemiological situation of chronic hepatitis B and revealed underestimation of assessments for the previous years. The continuing downward trend in the incidence of acute hepatitis B indicates the effectiveness of universal vaccination of newborns which is effective for 18 years and the sustainability of improvement in sanitary condition and compliance with safety precautions by medical personnel. In a situation when the majority of new infections still occur probably during medical procedures, it is recommended to execute vaccinations in all persons previously unvaccinated, especially those chronically ill and prior to planned surgeries.